The Palgrave Handbook of Philosophy and Public Policy (Springer International Publishing, 2018)
This book brings together a large and diverse collection of philosophical papers addressing a wide variety of public policy issues. Topics covered range from long-standing subjects of debate such as abortion, punishment, and freedom of expression, to more recent controversies such as those over gene editing, military drones, and statues honoring Confederate soldiers. Part I focuses on the criminal justice system, including issues that arise before, during, and after criminal trials. Part II covers matters of national defense and sovereignty, including chapters on military ethics, terrorism, and immigration. Part III, which explores political participation, manipulation, and standing, includes discussions of issues involving voting rights, the use of nudges, and claims of equal status. Part IV covers a variety of issues involving freedom of speech and expression. Part V deals with questions of justice and inequality. Part VI considers topics involving bioethics and biotechnology. Part VII is devoted to beginning of life issues, such as cloning and surrogacy, and end of life issues, such as assisted suicide and organ procurement. Part VIII navigates emerging environmental issues, including treatments of the urban environment and extraterrestrial environments.